Preparation method and application of cyclodextrin-loaded iron-aluminum bimetallic polymeric material
By adding anhydrous citric acid, potassium dihydrogen phosphate, iron salt and aluminum salt to the aqueous cyclodextrin solution, a cyclodextrin gel material loaded with iron and aluminum bimetals is formed, and the wastewater treatment in the prior art is solved The problem of poor results has achieved efficient removal of heavy metals and organic pollutants in water.
Patent Information
- Application Number
- CN202411216930.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art has poor removal effect of heavy metals and organic pollutants in wastewater treatment. The particles of nano zero-valent iron and nano zero-valent aluminum are prone to agglomeration, surface oxidation and reactive active sites are reduced, and the selective removal effect of pollutants. Not good.
The preparation method of cyclodextrin-loaded iron-aluminum bimetallic polymer material is adopted. The hydrothermal reaction is carried out by adding anhydrous citric acid, potassium dihydrogen phosphate, iron salt and aluminum salt to the aqueous cyclodextrin solution, and then the liquid phase reduction reaction is carried out. The cyclodextrin gel material with iron-aluminum bimetallic loading is formed to enhance its electron transfer performance and reactivity, and to improve dispersion and selective adsorption capacity through esterification and condensation reaction.
It significantly improves the electron transfer and catalytic performance of nanoparticles, increases the selective adsorption capacity of pollutants, reduces the oxidation of the surface of nanoparticles, and improves the removal efficiency of heavy metals and organic pollutants in water. It is suitable for water pollutants. Efficient processing.
Smart Images

Figure CN119303556A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental restoration materials, and in particular to a preparation method and application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material. Background Art
[0002] The rapid development of industry and agriculture has led to an increasing demand for the application of metals and organic compounds in various products and industries, resulting in widespread heavy metal and organic pollution in water bodies. Batteries, pigments, automobile fuels, photographic films, various explosives, coating materials, aviation and steel industries often cause a large amount of heavy metals to be released into the environment. The burning of fossil fuels, oil spills, tar gas processing, the large-scale use of pesticides and herbicides, etc., can easily cause the release of organic pollutants such as petroleum hydrocarbons, polycyclic aromatic hydrocarbons, pesticides, antibiotics and chlorinated hydrocarbons into water bodies. Many heavy metals and organic pollutants are toxic or carcinogenic, posing safety hazards to ecological safety and human health. Effectively separating and enriching unwanted heavy metal ions in the environment and removing or degrading organic pollutants in the environment remain very important but challenging tasks.
[0003] In recent years, environmental remediation materials such as nano-zero-valent iron and nano-zero-valent aluminum have been efficiently explored and applied. Both have the characteristics of small particle size, large specific surface area, strong reducibility, multiple surface sites and high reactivity, and have been widely used in the removal of heavy metals and organic pollutants in water bodies. Nano-zero-valent iron and zero-valent aluminum can efficiently adsorb heavy metals in water bodies through coordination, precipitation and co-precipitation, and can also remove halogen ions in compounds such as chlorinated hydrocarbons, acetochlor and atrazine through strong reduction. At the same time, both have strong electron-donating ability and have high application potential in catalytic activation of oxidants such as hydrogen peroxide and persulfate to remove organic pollutants. However, both have some inherent defects in environmental remediation: (1) Nanoparticles and magnetic effects make them easy to agglomerate and have weak migration ability; (2) The surface of nanoparticles is easily oxidized, and the surface passivation layer leads to a reduction in reactive sites; (3) Affected by the water chemical environment, the selective removal effect of pollutants is poor. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a preparation method and application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material, aiming to solve the technical problem of poor sewage treatment effect in the prior art.
[0005] In order to achieve the above object, the present invention is implemented by the following technical scheme: a method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material, comprising the following steps:
[0006] (1) adding anhydrous citric acid, potassium dihydrogen phosphate, iron salt and aluminum salt to the cyclodextrin aqueous solution, stirring and mixing in a boiling water bath to obtain a mixed solution;
[0007] (2) placing the mixed solution prepared in step (1) in a hydrothermal reactor, heating it at a preset temperature for a preset time, and cooling it to room temperature to obtain a mixed suspension of iron-aluminum bimetallic salt and cyclodextrin polymer through an esterification condensation reaction;
[0008] (3) adding an aqueous solution of sodium dithionite and KBH4 dropwise to the mixed suspension obtained in step (2) to obtain a second mixed solution, and performing a liquid phase reduction reaction under anaerobic conditions;
[0009] (4) The second mixed solution after the liquid phase reduction reaction in step (3) is centrifuged to obtain a solid precipitate by solid-liquid separation, and then the solid precipitate is washed with ultrapure water and ethanol respectively, and finally the solid precipitate is freeze-dried to obtain a cyclodextrin gel material loaded with iron-aluminum bimetallic.
[0010] According to one aspect of the above technical solution, the cyclodextrin in the cyclodextrin aqueous solution is one of α-CD, β-CD, γ-CD, HPCD and carboxymethyl-β-cyclodextrin, and the mass concentration of the cyclodextrin in the mixed solution is: 50g-100g / L.
[0011] According to one aspect of the above technical solution, the mass ratio of the potassium dihydrogen phosphate, the anhydrous citric acid, and the cyclodextrin is 1:2:4.
[0012] According to one aspect of the above technical solution, the iron salt is FeCl3 or FeSO4, and the molar concentration of the iron salt in the mixed solution is: 0.1-0.5 mol / L.
[0013] According to one aspect of the above technical solution, the aluminum salt is AlCl3 or Al2(SO4)3, and the molar concentration of the aluminum salt in the mixed solution is: 0.01-0.1 mol / L.
[0014] According to one aspect of the above technical solution, in step (2), the preset temperature is: 140°C-180°C, and the preset time is: 1-5 hours.
[0015] According to one aspect of the above technical solution, the molar concentration of KBH4 in the aqueous solution of KBH4 is: 1-2 mol / L, and the volume ratio of the aqueous solution of KBH4 to the mixed solution is: 1:1-1:4.
[0016] According to one aspect of the above technical solution, the molar concentration ratio of the sodium dithionite to the iron-aluminum bimetallic salt in the second mixed solution is 0.01-0.1.
[0017] According to one aspect of the above technical solution, the step of carrying out a liquid phase reduction reaction under anaerobic conditions specifically includes:
[0018] In an anaerobic environment with nitrogen introduced, the second mixed liquid is stirred to perform a liquid phase reduction reaction, wherein the stirring speed is 200-400 r / min, and the duration of the stirring reaction is 2-4 hours.
[0019] On the other hand, the present invention also provides an application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method in the above technical solution in sewage treatment.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: iron salt and aluminum salt are prepared into a new nano bimetallic composite material through a liquid phase reduction reaction and subjected to a sulfurization reaction, which significantly improves the electron transfer performance and reaction activity of individual nanoparticles, and increases the reduction performance and catalytic performance of the nanoparticles. Cyclodextrin, as a carrier and stabilizing material, increases the dispersibility of bimetallic nanoparticles and reduces the rapid oxidation of the surface of nanoparticles. At the same time, the host-guest inclusion complex of cyclodextrin increases the selective adsorption of pollutants by the composite material, which is less affected by the water environment, and can be used for the adsorption of heavy metals in water bodies, the adsorption of organic pollutants, and the efficient degradation of organic pollutants in water bodies by catalytic oxidants, and has a broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a comparison chart of the removal rates of heavy metals in water by the cyclodextrin-loaded iron-aluminum bimetallic polymer material and the comparative material in the sixth embodiment of the present invention;
[0022] Figure 2 This is a comparison chart of the removal rates of imidacloprid in water by the cyclodextrin-loaded iron-aluminum bimetallic polymer material and the comparative material in the seventh embodiment of the present invention;
[0023] Figure 3 It is a comparison chart of the removal rate of nitrate in water by the cyclodextrin-loaded iron-aluminum bimetallic polymer material and the comparative material in the eighth embodiment of the present invention;
[0024] Figure 4 It is a comparison chart of the removal rate of naphthalene in water body catalyzed by persulfate oxidation degradation by cyclodextrin-loaded iron-aluminum bimetallic polymer material and comparative material in the seventh embodiment of the present invention;
[0025] The following specific implementation manner will further illustrate the present invention in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0026] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive.
[0027] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0029] Embodiment 1
[0030] The first embodiment of the present invention provides a method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material, comprising the following steps:
[0031] Step (1) adding anhydrous citric acid, potassium dihydrogen phosphate, iron salt and aluminum salt to the cyclodextrin aqueous solution, stirring and mixing in a boiling water bath to obtain a mixed solution.
[0032] Specifically, in this embodiment, the cyclodextrin in the cyclodextrin aqueous solution is one of α-CD, β-CD, γ-CD, HPCD (carboxypropyl-β-cyclodextrin) and carboxymethyl-β-cyclodextrin. The mass concentration of cyclodextrin in the mixed solution is: 50g-100g / L.
[0033] Furthermore, in this embodiment, the mass ratio of the potassium dihydrogen phosphate, the anhydrous citric acid, and the cyclodextrin is 1:2:4. The iron salt is FeCl3 or FeSO4, and the molar concentration of the iron salt in the mixed solution is 0.1-0.5 mol / L. The aluminum salt is AlCl3 or Al2(SO4)3, and the molar concentration of the aluminum salt in the mixed solution is 0.01-0.1 mol / L.
[0034] The temperature of the boiling water bath is preferably 90-100°C.
[0035] Step (2) placing the mixed solution prepared in step (1) in a hydrothermal reactor, heating it at a preset temperature for a preset time, and cooling it to room temperature to obtain a mixed suspension of iron aluminum bimetallic salt and cyclodextrin polymer through an esterification condensation reaction. Specifically, in this step, the preset temperature is: 140°C-180°C, and the preset time is: 1-5 hours.
[0036] Step (3) Add the aqueous solution of sodium dithionite and KBH4 dropwise to the mixed suspension obtained in step (2) to obtain a second mixed solution, and perform a liquid phase reduction reaction under anaerobic conditions. Specifically, in this step, the molar concentration of KBH4 in the aqueous solution of KBH4 is 1-2 mol / L, and the volume ratio of the aqueous solution of KBH4 to the mixed solution is 1:1-1:4. The molar concentration ratio of the sodium dithionite to the iron-aluminum bimetallic salt in the second mixed solution is 0.01-0.1.
[0037] Furthermore, the above-mentioned step of carrying out liquid phase reduction reaction under anaerobic conditions specifically includes:
[0038] In an anaerobic environment with nitrogen introduced, the second mixed liquid is stirred to perform a liquid phase reduction reaction, wherein the stirring speed is 200-400 r / min, and the duration of the stirring reaction is 2-4 hours.
[0039] Step (4) centrifuges the second mixed solution after the liquid phase reduction reaction in step (3), obtains a solid precipitate by solid-liquid separation, washes the solid precipitate with ultrapure water and ethanol respectively, and finally freeze-dries the solid precipitate to obtain a cyclodextrin gel material loaded with iron-aluminum bimetallic.
[0040] In some application scenarios of this embodiment, the specific preparation process of the cyclodextrin-loaded iron-aluminum bimetallic polymer material is as follows:
[0041] (1) 6.0 g of citric acid, 12 g of hydroxypropyl-β-cyclodextrin, 3.0 g of potassium dihydrogen phosphate, 6.48 g of ferric chloride and 1.33 g of aluminum chloride were placed in a 500 mL round-bottom flask, 200 mL of ultrapure water was added, and the mixture was heated and stirred in a boiling water bath at 100° C. for 2 hours to prepare a mixed solution.
[0042] (2) The mixed solution obtained in the above step (1) is poured into a hydrothermal reactor with a specification of 500 mL, placed in an oven and heated at 160° C. for 4 hours, and cooled to room temperature to obtain a mixed suspension of iron-aluminum bimetallic salt and cyclodextrin polymer through an esterification condensation reaction.
[0043] (3) The mixed suspension obtained in the above step (2) was poured into a three-necked round-bottom flask with a specification of 500 mL, and nitrogen was introduced to remove bubbles in the solution. After half an hour, 2.2 g of sodium dithionite was added under nitrogen protection. 3.0 g of potassium borohydride (KBH4) was weighed and poured into 50 mL of ultrapure water. The potassium borohydride solution was slowly added dropwise to the mixed suspension in the three-necked round-bottom flask, and the mixture was stirred at a speed of 300 r / min for 3 hours to carry out a liquid phase reduction reaction.
[0044] (4) The mixed suspension after the liquid phase reduction reaction is centrifuged to obtain a solid precipitate by solid-liquid separation, and then the solid precipitate is washed with ultrapure water and ethanol respectively, and finally the solid precipitate is freeze-dried to obtain a cyclodextrin gel material loaded with iron-aluminum bimetallic.
[0045] In summary, the preparation method in the above-mentioned embodiment of the present invention prepares a new nano bimetallic composite material by a liquid phase reduction reaction of iron salt and aluminum salt and performs a sulfurization reaction, which significantly improves the electron transfer performance and reaction activity of individual nanoparticles, and increases the reduction performance and catalytic performance of the nanoparticles. Cyclodextrin, as a carrier and stabilizing material, increases the dispersibility of bimetallic nanoparticles and reduces the rapid oxidation of the surface of nanoparticles. At the same time, the host-guest inclusion complex of cyclodextrin increases the selective adsorption of pollutants by the composite material, is less affected by the water environment, can be used for the adsorption of heavy metals in water bodies, the adsorption of organic pollutants, and the efficient degradation of organic pollutants in water bodies by catalytic oxidants, and has a broad application prospect.
[0046] Embodiment 2
[0047] Embodiment 2 of the present invention provides a method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material. The principle of the preparation method in this embodiment is basically the same as that in Embodiment 1, except that:
[0048] In step (1), the cyclodextrin in the cyclodextrin aqueous solution is carboxymethyl-β-cyclodextrin, and its mass concentration in the mixed solution is 50 g / L. The iron salt is FeSO4, and its molar concentration in the mixed solution is: 0.1 mol / L; the aluminum salt is Al2(SO4)3, and its molar concentration in the mixed solution is: 0.01 mol / L. The temperature of the boiling water bath is 90°C.
[0049] The preset temperature of the esterification condensation reaction in step (2) is 140° C., and the preset time is 5 hours.
[0050] The molar concentration of KBH4 in the aqueous solution of KBH4 in step (3) is 1 mol / L, and the volume ratio of the aqueous solution of KBH4 to the mixed solution is 1:1; the molar concentration ratio of sodium dithionite to the iron-aluminum bimetallic salt in the second mixed solution is 0.01. During the liquid phase reaction, the stirring speed is 200 r / min and the duration is 4 hours.
[0051] Embodiment 3
[0052] Embodiment 3 of the present invention provides a method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material. The principle of the preparation method in this embodiment is basically the same as that in Embodiment 1, except that:
[0053] The cyclodextrin in the cyclodextrin aqueous solution in step (1) is α-cyclodextrin, and its mass concentration in the mixed solution is 100 g / L. The iron salt is FeSO4, and its molar concentration in the mixed solution is: 0.5 mol / L; the aluminum salt is AlCl3, and its molar concentration in the mixed solution is: 0.1 mol / L.
[0054] The preset temperature of the esterification condensation reaction in step (2) is 180° C., and the preset time is 1 hour.
[0055] The molar concentration of KBH4 in the aqueous solution of KBH4 in step (3) is 2 mol / L, and the volume ratio of the aqueous solution of KBH4 to the mixed solution is 1:4; the molar concentration ratio of sodium dithionite to the iron-aluminum bimetallic salt in the second mixed solution is 0.1. During the liquid phase reaction, the stirring speed is 400 r / min and the duration is 2 hours.
[0056] Embodiment 4
[0057] Embodiment 4 of the present invention provides a method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material. The principle of the preparation method in this embodiment is basically the same as that of the preparation method in Embodiment 1, except that:
[0058] The cyclodextrin in the cyclodextrin aqueous solution in step (1) is β-cyclodextrin.
[0059] Embodiment 5
[0060] Embodiment 5 of the present invention provides a method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material. The principle of the preparation method in this embodiment is basically the same as that in Embodiment 1, except that:
[0061] The cyclodextrin in the cyclodextrin aqueous solution in step (1) is γ-cyclodextrin.
[0062] Embodiment 6
[0063] Embodiment 6 of the present invention provides an application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method in the above embodiment in sewage treatment.
[0064] In this embodiment, the cyclodextrin-loaded iron-aluminum bimetallic polymer material is used to remove heavy metals in water. The specific application scenarios are as follows:
[0065] The circulating water of the desulfurization pool of a certain electroplating plant was collected, and the concentrations of Cu, Cd, Cr, Mn and Tl in the raw water were detected by ICP-AES / MS to be 120, 15, 25, 330 and 2.5 mg / L respectively. The heavy metal removal experiment was carried out in a 50mL centrifuge tube, the reaction solution was 30mL, and the adsorbents were selected from the cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method of Example 1, commercial zero-valent iron (50μm) and commercial zero-valent aluminum (50μm), and the dosage was set to 1.0g. The adsorption experiment was carried out in a constant temperature shaker, the temperature was set to 25℃, the speed was 150r / min, the reaction was 30min, and after the reaction was completed, high-speed centrifugation was used for solid-liquid separation, and the concentration was detected by ICP-AES / MS after passing through a 0.22μm water filter.
[0066] The results are as follows Figure 1 As shown, the removal efficiency of heavy metals by cyclodextrin-loaded iron-aluminum bimetallic polymer material is 4.8%-37% and 1.8%-41% higher than that of commercial zero-valent iron and zero-valent aluminum, respectively. This promotion effect is more obvious when removing Tl with a lower concentration. For Tl with a lower concentration, the removal effects of commercial zero-valent iron and zero-valent aluminum on Tl are 71% and 69%, respectively. The removal rate of Tl is increased to 98% by using the cyclodextrin-loaded iron-aluminum bimetallic polymer material prepared in Example 1 of the present invention.
[0067] Embodiment 7
[0068] Embodiment 7 of the present invention provides an application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method in the above embodiment in sewage treatment.
[0069] In this embodiment, the cyclodextrin-loaded iron-aluminum bimetallic polymer material is used to remove imidacloprid in water. The specific application scenarios are as follows:
[0070] Add 0.021g of cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method of Example 1 to a 50mL glass reaction bottle, then add 30mL of 10mg / L imidacloprid solution, adjust the solution pH to 3, 5, 7, 9 and 11 with dilute hydrochloric acid and sodium hydroxide solution, respectively, and place the glass reaction bottle in a constant temperature shaker for 4h, keeping the temperature at 25°C and the speed at 180r / min. Commercial zero-valent iron and zero-valent aluminum were used as controls, and three parallel experiments were set for each group. After the reaction, 1mL of the reaction solution was filtered through a 0.22μm water filter membrane, and the concentration of imidacloprid in the filtrate was determined by high performance liquid chromatography.
[0071] The results are as follows Figure 2 As shown, under different pH conditions, the removal efficiency of cyclodextrin-loaded iron-aluminum bimetallic polymer materials on imidacloprid was above 92%, indicating that the removal of imidacloprid by cyclodextrin-loaded iron-aluminum bimetallic polymer materials was less affected by pH. Compared with commercial nano zero-valent iron and nano zero-valent aluminum, the removal efficiency of CD-NZVI@NZVAl composite materials on imidacloprid increased by 0.3-0.7 times and 0.5-0.8 times, respectively, indicating that it can efficiently remove halogen compounds in water through reduction substitution and adsorption.
[0072] Embodiment 8
[0073] Embodiment 8 of the present invention provides an application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method in the above embodiment in sewage treatment.
[0074] In this embodiment, the cyclodextrin-loaded iron-aluminum bimetallic polymer material is used to remove nitrate from water. The specific application scenarios are as follows:
[0075] Add 0.05 g of the cyclodextrin-loaded iron-aluminum bimetallic polymer material prepared by the method of Example 1 to a 50 mL plastic centrifuge tube, then add 40 mL of a 20 mg / L nitrate solution, and place the centrifuge tube in a constant temperature shaker for 4 hours, maintaining the temperature at 25 ° C and the speed at 180 r / min. Commercial zero-valent iron, zero-valent aluminum and activated carbon were used as controls, and three parallel experiments were set for each group of experiments. After the reaction was completed, 1 mL of the reaction solution was filtered through a 0.22 μm water filter membrane, and the nitrate concentration in the solution was determined by ion chromatography.
[0076] The results are as follows Figure 3 As shown, the cyclodextrin-loaded iron-aluminum bimetallic polymer composite material has a nitrate removal rate of more than 90%, while the nitrate removal rates of commercial zero-valent iron, commercial zero-valent aluminum and activated carbon are 46%, 42% and 29% respectively, indicating that cyclodextrin-loaded iron-aluminum bimetallic polymer materials can also efficiently remove nitrate from water.
[0077] Embodiment 9
[0078] Embodiment 9 of the present invention provides an application of a cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method in the above embodiment in sewage treatment.
[0079] In this embodiment, the cyclodextrin-loaded iron-aluminum bimetallic polymer material is used to catalyze the oxidation and degradation of naphthalene in water by persulfate, and the specific application scenarios are as follows:
[0080] The cyclic experiment of continuous addition of naphthalene and intermittent addition of PS was used to evaluate the stability and long-term effectiveness of the cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method of Example 1, and the activation of PS to degrade naphthalene in water. All batch experiments were carried out in 40mL amber glass bottles, and the first reaction solution was 30mL, in which the concentration of naphthalene contained was 10mg / L, the composite material content was 0.5g / L, and the PS concentration was 5.0mmol / L. All reaction vials were shaken at 180r / min and 25°C. Samples were taken every 12 hours, and 0.3mL of naphthalene stock solution was added after each sampling, for a total of 15 times, and 3.0mL of PS stock solution was added after each 5 samplings, for a total of three times, using commercial zero-valent iron and zero-valent aluminum as controls. After each addition of the agent, the solution was collected using a disposable syringe, filtered through a 0.22μm microporous filter, and the initial concentration of naphthalene was determined by high performance liquid chromatography. The endpoint concentration of naphthalene was determined by the same method after each addition of the pollutant.
[0081] The results are as follows Figure 4 As shown in the figure, when PS is not added, after 4 cycles, the degradation effect of cyclodextrin-loaded iron-aluminum bimetallic polymer on naphthalene is still 100%, while the removal effect of commercial zero-valent iron and zero-valent aluminum activated PS on naphthalene is only 66% and 59%. After continuous addition of naphthalene and intermittent addition of PS, after 15 cycles, the degradation effect of cyclodextrin-loaded iron-aluminum bimetallic polymer on naphthalene can reach 76%, while the removal effect of commercial zero-valent iron and zero-valent aluminum on naphthalene is only 35% and 25%, indicating that cyclodextrin-loaded iron-aluminum bimetallic polymer can efficiently and long-term oxidatively degrade PAHs in water.
[0082] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0083] The above-described embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a cyclodextrin-loaded iron-aluminum bimetallic polymer material, characterized in that: The following steps are involved: (1) adding anhydrous citric acid, potassium dihydrogen phosphate, iron salt and aluminum salt to the cyclodextrin aqueous solution, stirring and mixing in a boiling water bath to obtain a mixed solution; (2) placing the mixed solution prepared in step (1) in a hydrothermal reactor, heating it at a preset temperature for a preset time, and cooling it to room temperature to obtain a mixed suspension of iron-aluminum bimetallic salt and cyclodextrin polymer through an esterification condensation reaction; (3) adding an aqueous solution of sodium dithionite and KBH4 dropwise to the mixed suspension obtained in step (2) to obtain a second mixed solution, and performing a liquid phase reduction reaction under anaerobic conditions; (4) The second mixed solution after the liquid phase reduction reaction in step (3) is centrifuged to obtain a solid precipitate by solid-liquid separation, and then the solid precipitate is washed with ultrapure water and ethanol respectively, and finally the solid precipitate is freeze-dried to obtain a cyclodextrin gel material loaded with iron-aluminum bimetallic.
2. The preparation method according to claim 1, characterized in that: The cyclodextrin in the cyclodextrin aqueous solution is one of α-CD, β-CD, γ-CD, HPCD and carboxymethyl-β-cyclodextrin, and the mass concentration of the cyclodextrin in the mixed solution is 50g-100g / L.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the potassium dihydrogen phosphate, the anhydrous citric acid, and the cyclodextrin is 1:2:
4.
4. The preparation method according to claim 1, characterized in that: The iron salt is FeCl3 or FeSO4, and the molar concentration of the iron salt in the mixed solution is 0.1-0.5 mol / L.
5. The preparation method according to claim 1, characterized in that: The aluminum salt is AlCl3 or Al2(SO4)3, and the molar concentration of the aluminum salt in the mixed solution is: 0.01-0.1 mol / L.
6. The preparation method according to claim 1, characterized in that: In step (2), the preset temperature is 140°C-180°C, and the preset time is 1-5 hours.
7. The preparation method according to claim 1, characterized in that: The molar concentration of KBH4 in the aqueous solution of KBH4 is 1-2 mol / L, and the volume ratio of the aqueous solution of KBH4 to the mixed solution is 1:1-1:
4.
8. The preparation method according to claim 1, characterized in that: The molar concentration ratio of the sodium dithionite to the iron-aluminum bimetallic salt in the second mixed solution is 0.01-0.
1.
9. The preparation method according to claim 1, characterized in that: The steps of carrying out liquid phase reduction reaction under anaerobic conditions specifically include: In an anaerobic environment with nitrogen introduced, the second mixed liquid is stirred to perform a liquid phase reduction reaction, wherein the stirring speed is 200-400 r / min, and the duration of the stirring reaction is 2-4 hours.
10. Use of a cyclodextrin-loaded iron-aluminum bimetallic polymer material obtained by the preparation method according to any one of claims 1 to 9 in sewage treatment.